100 ideas that changed design - Fiell, Charlotte 1965-; Fiell, Peter (London Laurence King Publishing, 2019)
This inspiring book chronicles the most influential ideas that have shaped industrial and product design. Written by two experts on modern design, it provides both a concise history of the subject, and offers a fascinating resource to dip into for the general reader. From the origins or modern design in the craft movements of the 19th and early 20th century and the changes brought about by mass production, the book traces the most important ideas in design through the modern movement and post-war consumer society to more recent ideas such as Open-Source Design and Biomimicry. Arranged in a broadly chronological order, the ideas are presented through fascinating text and arresting visuals, 100 Ideas that Changed Design explores when each idea first evolved and the subsequent impact it has had up to the present day.
Introduction -- 100 ideas that changed design. No. 1 Innovation ; No. 2 Portability ; No. 3 Modularity ; No. 4 Standardization ; No. 5 Systemization ; No. 6 Style ; No. 7 Luxury ; No. 8 Creative expression ; No. 9 Aesthetics ; No. 10 Decoration ; No. 11 Taste ; No. 12 Utility ; No. 13 Industrial design ; No. 14 Product durability ; No. 15 Mass production ; No. 16 Division of labour ; No. 17 Universality ; No. 18 American system of manufacture ; No. 19 Design right protection ; No. 20 Historicism ; No. 21 Art manufacture ; No. 22 Design education ; No. 23 Design reform ; No. 24 Revealed construction ; No. 25 Fitness for purpose ; No. 26 Truth to materials ; No. 27 Simplicity ; No. 28 Rightness ; No. 29 Morality ; No. 30 Design rhetoric ; No. 31 Vernacularism ; No. 32 Ideal form ; No. 33 Democratic design ; No. 34 Design consultancy ; No. 35 The brief ; No. 36 There is always a better way of doing things ; No. 37 Form follows function ; No. 38 Functionalism ; No. 39 Design management ; No. 40 Total design ; No. 41 Unity ; No. 42 Gesamtkunstwerk ; No. 43 Ornament and crime ; No. 44 Purity ; No. 45 Rationalism ; No. 46 Taylorism ; No. 47 Fordism ; No. 48 Semiotics ; No. 49 Colour theory ; No. 50 Modern movement ; No. 51 New objectivity ; No. 52 Less is more ; No. 53 Lightness ; No. 54 Aerodynamics ; No. 55 Quality control ; No. 56 Packaging ; No. 57 Customization + Mass customization ; No. 58 Disposability ; No. 59 Styling ; No. 60 Streamlining ; No. 61 Fashion-led design ; No. 62 Planned obsolescence ; No. 63 Process-led design ; No. 64 Organic design ; No. 65 Ergonomics ; No. 66 Functional intuitiveness ; No. 67 Connections ; No. 68 Safety ; No. 69 Object trouv?e (the found object) ; No. 70 Character ; No. 71 Miniaturization ; No. 72 Branding ; No. 73 The world of tomorrow ; No. 74 Clarity of layout ; No. 75 Good design ; No. 76 Sustainability ; No. 77 Anti-design ; No. 78 Pop ; No. 79 Less is a bore ; No. 80 Design hacking ; No. 81 Human-centred design ; No. 82 Inclusive design ; No. 83 The iconic design ; No. 84 Robotics ; No. 85 Biomimicry ; No. 86 Interface / Interaction design ; No. 87 Green design / Greenwash ; No. 88 Recycling + upcycling ; No. 89 Essentialism ; No. 90 Design art ; No. 91 Transparency ; No. 92 Digitalization ; No. 93 CAD/CAM ; No. 94 Convergence of functionality ; No. 95 3D printing ; No. 96 Open-source design ; No. 97 Parametricism ; No. 98 Haptics ; No. 99 Smart machines (AI + ML) ; No. 100 IOT (The internet of things) -- Notes -- Further reading.
Prof. San Pedro (Recommending faculty)- Bookfair 2019
Includes bibliographical references and index.
Keywords: Design -- Pictorial works; Product design -- Pictorial works; Decorative arts; Design -- History; Design -- Technological innovations